Cyclic visualization of the respiratory stages in teaching human physiology to english-speaking students - M. Povar; S. Tkachuk; O. Yasinska (Kazimierz Wielki University, 2022)
In the course of Human Physiology, students of different specialties learn cyclic processes reflecting the work of the cardiovascular, respiratory, female reproductive systems and sleep as well. Visualization of the cyclic processes is essential for better understanding of the organization and functioning of these systems and finding pathological deviations with formation of defective cycles. The objective of the work is to analyze the application of the visualization of the respiratory stages into the educational process. Dynamics of the physiological processes at various stages of respiration with the help of schematic visual figures allows effective formation of the students' systemic understanding of the respiratory system functions and its interrelations with the cardiovascular system.  These enable to apply the acquired theoretical knowledge while solving clinical situational tasks and formation of professional competence.